Value Incompatibility in the Medical Workplace: The Erosion of Cooperation and the Impact on Clinical Safety - Michailidou, Evangelia Michail (British Journal of Healthcare and Medical Research, 2026)
This opinion Partners in Precision: Cultivating Trust and Respect in the Surgeon- Anesthetist Dynamics article examines the phenomenon of ethical incompatibility within medical teams. It analyzes the dynamics of betrayed trust and gossip, while proposing specific administrative protocols for addressing toxicity, with the aim of safeguarding patient safety and the prestige of the medical profession.